Speech acts, strategies and leadership values in Obama’s apology discourse - Raja Ravi Varma, Susanna Bithiah Varma (2018)
Much of the research on leadership has focused on gaining an understanding of what constitutes effective leadership. These research, however, approach leadership from the aspect of organisation and management focusing on performance of leaders mainly on traits and behaviours of effective leaders. Although discourse has been long acknowledged as a crucial aspect of leadership performance, only few studies in recent years have begun to examine leadership from the perspective of discourse. These research suggest an intricate relationship between language and leadership. The present study addresses this gap in its aims to explore how leadership is displayed linguistically through the discourse of apology. The study analyses leadership apologies in order to gain insights into effective leadership performance from the perspective of apologising as an act. Habitually, leaders seldom apologize. However, a growing body of literature suggests that leaders are not only vulnerable to making mistakes, but they maybe more prone to make mistakes because of the complexity of their position. In fact, one displays the maturity of leadership by being enough of a leader to own up to one’s mistakes and apologize. Apology is, in fact, a leadership behavior and practice. This study focuses on Barack Obama as a politician and examines his apology discourse for leadership qualities. The study examines the speech acts and apology strategies that are used to construct his apologies, and the leadership values that emerge. The study relies on Speech Act theory (Searle, 1969) and Grounded Theory (Strauss and Corbin, 1990). The research design is qualitative and the data was collected through purposive sampling. Two apologies of Obama were obtained from electronic websites based on their availability of text and extensive news coverage for contextual information to assist in the understanding of the case study of each apology. The study employed pragmatics and positive discourse analysis as approaches to discourse analysis. Suitable frameworks of analysis were used, mainly Searle’s (1969) framework for illocutionary speech acts, Murphy’s (2014) framework for apology, Fairclough’s (1995) and Halliday and Hassan’s (1976) techniques for lexical analysis to establish leadership values. The findings revealed that the use of speech acts and strategies varied and were based on the intensity of the crisis in both apologies. The findings also found ‘dual’ speech acts which are a combination of two speech acts such as ‘representative declarative’ and ‘representative commissive’. The new finding to the apology strategies were the emergence of two other strategies; ‘To sympathize/recognize victim’s affliction’ and ‘To appreciate/comfort/conciliatory expression’. Both texts had an array of values birthed out from different apology situations through the speech acts and strategies. Among the values found were responsibility, determination and dedication to duty, trustworthiness and truthfulness, regretful, and appreciative of the victim’s service/sacrifice. The study determined the leadership styles of Obama through his use of speech acts, strategies and leadership values. The findings showed that both transactional and transformational were styles that helped Obama in performing the apology. The study then concluded that leadership should be versatile for a leader to be able to perform efficiently in crucial situations. It is important for a leader to have the ability to blend acts and strategies to display good values to perform the speech act of apology well. A leader should have the awareness and knowledge on how to apologize effectively because in doing so, they will be able to bind themselves well in good rapport with their followers which creates unity in the relationship. The significance of the study can be viewed in the potential to reframe apology as an empowering and favorable act that can positively impact leaders’ image rather than an act that is viewed as taboo or ineffective for leadership.